Characterization of genetic‐origin‐dependent monoallelic expression in mouse embryonic stem cells. (11th December 2019) - Ohishi, Hiroaki; Au Yeung, Wan Kin; Unoki, Motoko; Ichiyanagi, Kenji; Fukuda, Kei; Maenohara, Shoji; Shirane, Kenjiro; Chiba, Hatsune; Sado, Takashi; Sasaki, Hiroyuki
Abstract: Monoallelic gene expression occurs in various mammalian cells and can be regulated genetically, epigenetically and/or stochastically. We identified 145 monoallelically expressed genes (MoEGs), including seven known imprinted genes, in mouse embryonic stem cells (ESCs) derived from reciprocal F1 hybrid blastocysts and cultured in 2i/LIF. As all MoEGs except for the imprinted genes were expressed in a genetic‐origin‐dependent manner, we focused on this class of MoEGs for mechanistic studies. We showed that a majority of the genetic‐origin‐dependent MoEGs identified in 2i/LIF ESCs remain monoallelically expressed in serum/LIF ESCs, but become more relaxed or even biallelically expressed upon differentiation. These MoEGs and their regulatory regions were highly enriched for single nucleotide polymorphisms. In addition, some MoEGs were associated with retrotransposon insertions/deletions, consistent with the fact that certain retrotransposons act as regulatory elements in pluripotent stem cells. Interestingly, most MoEGs showed allelic differences in enrichment of histone H3K27me and H3K4me marks, linking allelic epigenetic differences and monoallelic expression. In contrast, there was little or no allelic difference in CpG methylation or H3K9me. Taken together, our study highlights the impact of genetic variation including single nucleotide polymorphisms and retrotransposon insertions/deletions on monoallelic epigenetic marks and expression in ESCs. Abstract : We identified genetic‐origin‐dependent monoallelically expressed genes in mouse embryonic stem cells. Our study highlights the impact of genetic variation including single nucleotide polymorphisms (SNPs) and retrotransposon insertions/deletions on monoallelic epigenetic marks and expression in mouse embryonic stem cells.